Effect of Ginger and Thyme Essential Oils as an Alternative to Antibiotic Growth Promoters on Performance, Immune Status and Economics of Broiler Production - Sampate, A. S.; Nikam, M. G.; Dhumal, M. V.; Deshpande , K. Y.; Gaikwad, S. S. (International Journal of Livestock Research, 2019)
An experiment was conducted on 300-day old Vencobb-400 straight run chicks which were weighed and distributed randomly into five treatment groups viz. A, B, C, D, and E with four replicates of 15 chicks each. The treatment group A was without essential oil and antibiotic. The treatment groups B was with growth promoting antibiotic (BMD) @ 30 mg/kg of feed and without EOs. The treatment groups C, D and E were with Thyme oil @50mg /kg, Ginger oil @25mg/kg and Thyme oil @50mg /kg + Ginger oil @25mg/kg of feed, respectively. The cumulative weight gain was significantly affected (P <0.05) by supplementation of essential oils, however, feed consumption and feed conversion ratio were found to be non-significant. Ginger oil @ 25mg/kg supplemented group (D) had numerically higher antibody titer against IBD but the differences were statistically non-significant. The net profit per bird was highest for ginger oil group D compared to control. The results inferred that ginger oil @ 25 mg/kg of feed improved profitability and immune status. It may be used as alternative to antibiotic growth promoters.